Bureaucratic behaviour, and its influence towards competitiveness – analysing the supply chain of Bangladeshi clothing industry - Nuruzzaman, Md.; Haque, A. K. M. Ahasanul; Shamsuddoha, Mohammad (UNIMAS Publisher, 2023)
Distribution systems are becoming increasingly complex and dynamic in business in the consumer market of clothing or Readymade Garments (RMG) products. There are many exterior influencing elements like political action (PA), country risk (CR), and bureaucratic behaviours (BB) that are influencing the clothing supply chain and posing threats to its competitiveness. A research question has developed to know how BB activities affect competitiveness. Based on this research question, this research aims to determine BB’s influence on the competitiveness of the clothing supply chain. Stakeholder philosophies and resource dependence theory have been considered to develop a hypothesis in this study. The Quantitative research method was applied in this study. The data were collected through a field survey. Partial Least Squire (PLS) based Structural Equation Modelling (SEM) was used to analyse collected data. Seven hypotheses were developed in this research. Among them, five hypotheses are supported, and two hypotheses are not supported. In addition, mediation test results are not reflected as positive. The findings are discussed in detail in the discussion and implementation part of this study. The clothing (RMG) industry of Bangladesh could implement the result to improve competitiveness.